Alpha-Asaronol Alleviates Dysmyelination by Enhancing Glutamate Transport Through the Activation of PPARγ-GLT-1 Signaling in Hypoxia-Ischemia Neonatal Rats - Ge, Yuhang; Zhen, Fei; Liu, Ziqi; Feng, Zhaowei; Wang, Gui; Zhang, Chu; Wang, Xingqi; Sun, Ying; Zheng, Xiaohui; Bai, Yajun; Yao, Ruiqin (Frontiers in Pharmacology, 2022)
Preterm white matter injury (PWMI) is the most common form of brain damage in premature infants caused by hypoxia-ischemia (HI), inflammation, or excitotoxicity. It is characterized by oligodendrocyte precursor cell (OPC) differentiation disorder and dysmyelination. Our previous study confirmed that alpha-asarone (α-asaronol), a major compound isolated from the Chinese medicinal herb Acorus gramineus by our lab, could alleviate neuronal overexcitation and improve the cognitive function of aged rats. In the present study, we investigated the effect and mechanism of α-asaronol on myelination in a rat model of PWMI induced by HI. Notably, α-asaronol promoted OPC differentiation and myelination in the corpus callosum of PWMI rats. Meanwhile, the concentration of glutamate was significantly decreased, and the levels of PPARγ and glutamate transporter 1 (GLT-1) were increased by α-asaronol treatment. In vitro, it was also confirmed that α-asaronol increased GLT-1 expression and recruitment of the PPARγ coactivator PCG-1a in astrocytes under oxygen and glucose deprivation (OGD) conditions. The PPARγ inhibitor GW9662 significantly reversed the effect of α-asaronol on GLT-1 expression and PCG-1a recruitment. Interestingly, the conditioned medium from α-asaronol-treated astrocytes decreased the number of OPCs and increased the number of mature oligodendrocytes. These results suggest that α-asaronol can promote OPC differentiation and relieve dysmyelination by regulating glutamate levels via astrocyte PPARγ-GLT-1 signaling. Although whether α-asaronol binds to PPARγ directly or indirectly is not investigated here, this study still indicates that α-asaronol may be a promising small molecular drug for the treatment of myelin-related diseases.